2008
DOI: 10.1016/j.cub.2008.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Face-Processing Strategies in Parents of Autistic Children

Abstract: Summary In his original description of autism, Kanner [1] noted that the parents of autistic children often exhibited unusual social behavior themselves, consistent with what we now know about the high heritability of autism [2]. We investigated this so-called “Broad Autism Phenotype” in the parents of children with autism, who themselves did not have a diagnosis of any psychiatric illness. Building on recent quantifications of social cognition in autism [3], we investigated face processing using the “Bubbles”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 24 publications
(36 reference statements)
4
101
1
1
Order By: Relevance
“…Although the experimenter closely monitored participants' gaze patterns to ensure that relatives from both groups were carefully inspecting the faces, it remains possible that relatives of children with ASD were attending to different parts of the faces compared with relatives of typically developing children. Adolphs et al (2008) showed that some parents of children with autism required more information from the mouth and less information from the eyes than parents of typically developing children to judge emotions. Perhaps, then, our relatives of children with ASD were not attending to the ''right'' part of the face.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the experimenter closely monitored participants' gaze patterns to ensure that relatives from both groups were carefully inspecting the faces, it remains possible that relatives of children with ASD were attending to different parts of the faces compared with relatives of typically developing children. Adolphs et al (2008) showed that some parents of children with autism required more information from the mouth and less information from the eyes than parents of typically developing children to judge emotions. Perhaps, then, our relatives of children with ASD were not attending to the ''right'' part of the face.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important for future studies to examine the relationship between degree of genetic liability and face-coding atypicalities more directly, by using larger samples, by controlling for family composition and by including dimensional ratings of autisticlike traits (cf. Adolphs et al, 2008, see Pellicano, 2008. Doing so should provide greater clarity regarding the neurocognitive pathways involved in the genetic liability for autism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in ASD as for other psychiatric disorders that are phenotypically complex and highly heritable, there is a growing consensus that research into the aetiology of the condition could benefit from the investigation of heritable markers (or endophenotypes, see Gottesman and Gould, 2003), that is traits that are also present in unaffected biological relatives of ASD but exhibited to a lesser degree (Adolphs et al, 2008;Geschwind, 2009;Sucksmith et al, 2011). In this domain of research, the so-called Broader Autism Phenotype (BAP), mild social and communication impairments have been suggested to be likely 'the most familial of autism-related traits' (Gerdts and Bernier, 2011, p.14).…”
Section: Introductionmentioning
confidence: 99%